PRODUKSI RUMPUT SUDAN DAN PERHITUNGAN EKONOMI PENGGUNAAN PUPUK NITROGEN, FOSFOR, DAN KALIUM: SUDAN GRASS PRODUCTION AND ECONOMIC ANALYSIS OF NITROGEN, PHOSPHOR. POTASIUM FERTILIZERS UTILIZATION - Onesimus Yoku; Djoko Soetrisno; Syamsul Arifin Siradz (Fakultas Peternakan Universitas Papua, 2010)
The aim of this study were to obtain the optimum level of NPK fertilizers of sudan grass and economic of NPK fertilizers utilization. The randomized completely block design (RCBD) were used to evaluate, namely 4 levels of fertilizer doses NPK and 4 blocks for determine the grass production. The treatments for randomly N application, namely: No (PO); N150 (P1); N300 (P2); and N450(P3). Phosphorus and K fertilizer were given at the same rate, that were 300 kg P2O5 and 150 kg K2O ha-1. The results of study showed that DM production for PO (3.19 tonha-1) differed significantly with P1, P2 and P3; but between P2 and P3 did not differ significantly. There were increased DM production due to increasing of fertilizers applied. The values of DM production increasing percentage for P1, P2, and P3 compared with PO, for DM were 69.44%, 80.45% and 85.28%, respectively. The increased percentages of DM production of P3 tended to decrease. Therefore, it can be summarized that P2 (300 kg N, 300 kg P and 150 kg K ha-1) was optimum level for DM production. Based on partial budget analysis, indicated that cultivation of sudan grass with NPK fertilizer treatments yielded profit positively. The profit value for P1, P2, and treatment of P3 were Rp 581.500,-; Rp 2.009.500,-; and Rp 2.997.500,-per hectare, respectively.